Republic of Congo - Joint World Bank-IMF Debt Sustainability Analysis Update : July 2019 - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Based on an assessment of external public debt indicators and given the continued buildup of external arrears, the Republic of Congo is classified as “in debt distress”. Moreover, despite the recent restructuring agreement with China, public debt remains unsustainable with the net present value of external debt in percent of gross domestic product (GDP) and the external debt service-to-revenue ratios projected to remain above their indicative thresholds in the medium ter